Family Centered Care Berhubungan dengan Kepuasan dan Kecemasan Keluarga Pasien TB Paru - Ningrum, Sefia; Palupi, Rini; Kusuma, Anggi (Fakultas Ilmu Kesehatan, 2025)
Tuberculosis (TB) is an infectious disease that requires family assistance in the treatment process. At this time, the patient's family will feel anxious, so there is a need for family-centred care (FCC). Fulfillment of FCC will have an impact on satisfaction for patients, families and health workers. The aim of this research is to determine the relationship between family centered care and satisfaction and anxiety of families of pulmonary TB patients in the pulmonary ward of Jend General Hospital. Ahmad Yani Metro.This type of research is quantitative descriptive correlation research design, with a cross sectional approach. The population in this study were families of pulmonary TB patients with a sample of 80 people using a total sampling technique. Analysis of this data was carried out using the chi square test and gamma correlation test, where the results of the family centered care distribution were mostly in the good category, 60 (75%), satisfaction in the satisfied category, 68 (85%), in the mild anxiety category, 40 (60%). The results of bivariate analysis show that there is a relationship between family centered care and family satisfaction of pulmonary TB patients with a p-value of 0,000. And there is a relationship between family centered care and family anxiety, with a p-value of 0,003, with a correlation level of 0,578, which means a positive relationship at a moderate level. Suggestions from the results of this research can provide input to focus on services that involve families and can work together between patient family members and nurses to provide effective and efficient health services.